Identified unmet needs and proposed solutions in mild‐to‐moderate haemophilia: A summary of opinions from a roundtable of haemophilia experts. (1st February 2021) - Walsh, Christopher; Boggio, Lisa; Brown‐Jones, Lanette; Miller, Rachel; Hawk, Sarah; Savage, Brittany; Hansen, Kerry; Molter, Don; Baumann, Kim; Dunn, Spencer; Skinner, Mark W.; Haugstad, Kimberly; et al.
Abstract: Introduction: The experiences of patients with mild‐to‐moderate haemophilia differ from those of patients with severe haemophilia or those without a bleeding disorder and include a challenging diagnosis and variability in bleeding symptoms and treatment needs. In addition, there is a significant lack of data on mild‐to‐moderate haemophilia, and many unmet needs remain to be identified and addressed in this group of patients. Methods: Challenges for these patients, including women with haemophilia, were identified during a roundtable meeting attended by a group of US‐based experts including healthcare professionals (e.g., physicians, nurses, and physical therapists) and patients who live with a bleeding disorder. Results: Identified unmet needs included a lack of proper education on the management of their disorder and prompt treatment of bleeds, absenteeism from school and work, and challenges with personal relationships. Initiatives to assist with alleviating these unmet needs were proposed and include suggestions for healthcare professionals, haemophilia treatment centres (HTCs) and national and local organizations within the bleeding disorders community. These included HTC and community engagement programmes for patients with mild‐to‐moderate haemophilia, revised transition guidelines for these patients as they approach adulthood and revised diagnostic classification of mild and moderate haemophilia. Challenges unique to women with haemophilia and ways to address these issues were also discussed. Conclusion: This paper summarizes the challenges, initiatives and suggestions that were identified by the haemophilia experts during the roundtable meeting.